Surgical and functional outcomes of vancouver type B2 postoperative periprosthetic femoral fracture treated with revision arthroplasty and coxa femoral bypass - Chatrashali, Shivaraj Amruthrao; Gaddi, Rakshith Amaresh (International Journal of Research in Orthopaedics, 2024)
As the number of total hip arthroplasties have steadily increased, one would expect a concomitant increase in catastrophic postoperative events such as periprosthetic fractures. This study evaluates the surgical and functional outcome, along with the associated complication rates in patients undergoing revision arthroplasty following Vancouver type B2 post-operative periprosthetic femoral fracture. We studied 14 Clinically and radiologically diagnosed patients with Vancouver type B2 Post-operative Periprosthetic femoral fracture. The post-operative VAS score has decreased to 2.23±0.92 from a pre-operative score of 8.30±0.9, p<0.001. The average Harris Hip Score has improved from 44.05±7.71 pre-operatively to 83.63±7.75 post-operatively at 6 months, p<0.001. At 6-month follow-up, we had 57% excellent results, 29% good results, 7% fair results, and 7% poor results based on Harris Hip Score. The revision arthroplasty of Vancouver type B2 post-operative periprosthetic femoral fracture with revision arthroplasty and coxa femoral bypass has excellent-good surgical as well as functional outcomes in terms of regaining abductor function by an increase in range of motion at the affected hip joint, significant pain relief leading to improved quality of life after surgery at short term follow up period.